Cognitive style and drinking to cope: A prospective cohort study. (29th September 2021) - Corcoran, Emma; Lewis, Gemma; Heron, Jon; Hickman, Matthew; Lewis, Glyn
Abstract: Background and Aims: Having a negative cognitive style may lead someone to feel hopeless about his or her situation and be more likely to engage in coping‐motivated drinking. We, therefore, aimed to investigate the association between cognitive style and drinking to cope. Design: Prospective cohort study. Setting: The former Avon Health Authority in South West England. Participants: A total of 1681 participants of the Avon Longitudinal Study of Parents and Children. Measurements: Participants completed cognitive style questions at age 17 and a subset of drinking to cope questions at age 24. We used linear regression to test the association between cognitive style and drinking to cope, controlling for confounders. Alcohol consumption and dependence scales were included in a secondary analysis. Findings: A 20‐point increase (that was the standard deviation of the exposure variable) in cognitive style score at age 17 was associated with an increase of 0.24 in drinking to cope scores at age 24 after adjustment for confounding variables (95% CI) = 0.08–0.41, P = 0.003). We found no evidence of an association between cognitive style and alcohol consumption (coefficient = 0.03, 95% CI = −0.08–0.14, P = 0.591) before or after adjustment. There was evidence for an association with alcohol dependence, but this was not present after adjusting for confounders (coefficient = 0.01, 95% CI = −0.04–0.05, P = 0.769). Conclusions: In young adults in England, there appears to be a positive association between negative cognitive style and subsequent drinking to cope.